Meningkatkan Ekspor Kerajinan Tembaga Dengan Teknologi Digital Di Desa Tumang Kecamatan Cepogo Kab.Boyolali - Nabyla Aulya; Alfian Arif Nugroho; Iqhbal Dwi Cahyo; Maria Kristina Laura Roja; Sri Budi Raharjo (Pusat Riset dan Inovasi Nasional, 2025)
Export is an activity of sending, issuing goods or services from within the country to abroad. Export has an important role for the country because it can increase national income. Tumang has long been known as a center for copper crafts that have high artistic value and unique cultural appeal. Currently, crafts made from metals such as copper, silver, aluminum are still maintained and developed in Indonesia, are a valuable cultural heritage passed down from generation to generation. In today’s increasingly sophisticated era with very rapid advances in technology and communication, the use of marketing through social media is the main choice for business people. Even though current technological advances are very fast, there are still several micro copper craft businesses that have not utilized digital technology. Digital marketing for copper crafts is the right marketing solution and strategy, and analytics to reach target audiences effectively. The goal is to increase brand awareness, expand marketing reach, build customer relationships and increase conversions and sales. The main goal of digital marketing is to increase brand presence in the digital world, help businesses reach a wider audience, and make brands known to potential consumers.